Christopher Cotter and David Robertson of The Religious Studies Project. (9th November 2020) - Newton, Richard; Cotter, Christopher; Robertson, David
Abstract : The Religious Studies Project is now a well-known fixture in the field, but it was not always as well-known as it is today. In this interview, Dr. Richard Newton from the Bulletin sat down with Dr. Chris Cotter and Dr. David Robertson to discuss their journey in creating the religious studies podcast from simple pub talk in 2010 to its current collection of some 300 episodes. In relaying their strides and struggles in this venture, Cotter and Robertson answer many of the questions that prominently face scholars in digital work and help showcase the need for such methods to gain acceptance in an academic world whose needs are swiftly changing.